Activation energy mediated band structure in strained multiferroic BiFeO3 thin films. Issue 5 (1st April 2020) - Shao, F.; Chen, J.K.; Chew, K.H.; Zhao, G.L.; Ren, Z.Y.; Liu, P.F.; Liu, Q.; Teng, J.; Xu, X.G.; Miao, J.; Jiang, Y.
Abstract: Although improved magnetic and piezoelectric performances were discovered in BiFeO3 rhombohedral-tetragonal mixed-phase, the associated electronic conduction mechanisms are less investigated. In the present work, we systematically investigated the leakage current and dielectric response as a function of temperature, frequency and bias field for pure rhombohedral and rhombohedral-tetragonal mixed-phase BiFeO3 films grown by pulse laser deposition. The multiferroic properties are demonstrated from their polarization and magnetization hysteresis. Both current-voltage and dielectric relaxation measurements indicate a lower activation energy observed for the mixed-phase BiFeO3 as compared to the rhombohedral-phase one. The present work for the first time indicates the distinguished transport properties as governed by different electronic conduction mechanisms for BiFeO3 at various phases, and improves the understandings associated to the strain engineering related electrical properties.